Analyzing the Link between Population Diversity, Population Growth, and Income: A Panel Data Study - Firdaus, Irfan Aziz Al; Pradana, Cokorda Bagus Ghana Indra; Sugiyanto, Catur (Journal of Indonesian Economy and Business, 2026)
Introductions: Amidst shifting demographics across many countries, certain stylized facts related to fertility, population, and income have become less universally applicable as previously established empirical models of fertility were based on long-standing regularities—namely, the negative relationships between income and fertility as well as between women’s labor force participation and fertility—many of which are now being reconsidered in light of evolving demographic trends. Novelty: This research addresses a significant gap in the literature by providing a comprehensive analysis of the relationship between population diversity, population growth, and income growth, incorporating both time-varying and cross-country components. While existing studies have examined these factors individually, our study integrates them to offer a more complete understanding of their interactions. Methodology: We employ the system generalized method of moments (GMM), a dynamic panel estimation technique that helps address endogeneity and unobserved heterogeneity in panel data settings. Findings: Our findings reveal a positive correlation between population diversity and population growth, suggesting that diversity and migration contribute to population expansion through strategic interactions among ethnic groups competing for influence in society, fostering pro-birth policies. However, we also find a negative association between population diversity and income growth, indicating potential ethnic conflict and rent-seeking behavior. In highly diverse societies, rent-seeking can lead to underinvestment in public goods, while frequent ethnic conflict is linked to lower economic growth. Conclusion: This paper highlights the complex relationship between diversity, demographic trends, and economic outcomes, underscoring the need for further research on mitigating the adverse effects of diversity on income growth.